Introduction to podopediatrics - Thomson, Peter, DPodM; Volpe, Russell G.; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2001)
INTRODUCTION TO PODOPEDIATRICS, 2/E is a concise but comprehensive introduction to the effective care of foot problems in children. Including coverage of the general, specialist and medical conditions which may influence the course of the podiatric treatment. Written by a multidisciplinary, international team of contributors under the editorship of a UK practitioner and and American educator and practitioner -- both podiatrists.
Section 1: -- Psychological considerations in the child patient -- Growth and development -- History-taking and the physical examination -- Paediatric gait -- Section 2: -- General medicine and diabetes -- Rheumatic diseases of childhood and adolescence -- Paediatric neurology -- Cutaneous diseases in childhood -- Section 3: -- Radiological examination of the child's foot -- Orthopaedic conditions affecting the foot in childhood -- Torsional and frontal plane conditions of the lower extremity -- Developmental flatfoot. -- Section 4: -- Physical therapy -- Serial casting -- Orthotic management -- Sports injuries. -- APPENDICES -- Appendix 1 Special investigations -- Appendix 2 Examples of recognised human teratogens -- Appendix 3 Autosomal dominant disorders -- Appendix 4 Autosomal recessive disorders -- Appendix 5 X-linked disorders -- Appendix 6 Developmental milestones -- Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Children -- Diseases -- Treatment; Pediatrics; Podiatry; Foot -- Diseases; Pédiatrie.; Podologie; Pied; Children -- Diseases -- Treatment; Foot -- Diseases; Pediatrics; Podiatry; Foot Diseases; Child; Foot Deformities, Congenital; Infant; Electronic books